Case Of Multiple Infantile Hemangioma in An Infant - Kumar, Ganesh; Pande, Vineeta; D S, Darshana; Mane, Shailaja; Khan, Owais Ali; Garlpati, Srinija (Journal of Neonatal Surgery, 2025)
Infantile hemangioma is a common benign vascular tumor that typically appears in infants shortly after birth. It affects 5% to 10% of all infants born. (1) These lesions can vary in size, shape, and location but normally follow a pattern of rapid growth followed by involution. While most infantile hemangiomas do not require treatment, early recognition and understanding the natural course of these lesions are important for appropriate management and guidance for affected infants and their families. This case report describes an infant who presented with infantile hemangiomas which were multiple in number. This case reports discusses the significance and course of such lesions, along with the need for guidance of the parents